A Concise Companion to Postcolonial Literature - Chew, Shirley; Richards, David (Malden, MA : Wiley Blackwell, 2014)
This Concise Companion offers an innovative, multi-disciplinary approach to Postcolonial literatures and cultures from 1947 to the present. In a series of original essays, leading international scholars, including C.L. Innes and Susan Bassnett, seek to explore and explain the ideas and practices that have emerged from the dismantling of European empires, and the impact that these have on Postcolonial literatures and cultures. This authoritative Companion investigates the key concerns of and the politics of resistance. Individual chapters focus on a broad range of subjects such as identity studies, orality, and literacy, nationalisms, feminism, anthropology and cultural criticism, the politics of rewriting, new geographies, publishing and marketing, and translation studies. A Concise Companion to Postcolonial Literature is an indispensable guide for anyone seeking an authoritative understanding of the intellectual contexts of Postcolonialism.
List of Illustrations ; Notes on Contributors ; Introduction. Chapter 1- Framing Identities -- Chapter 2 - Orality and Literacy ; Part 1 - India ; Part 2 - South Africa -- Chapter 3 - Politics of Rewriting -- Chapter 4 - Postcolonial Translations -- Chapter 5 - Nation and Nationalisms -- Chapter 6 - Feminism and Womanism; Chapter 7 - Cartographies and Visualization -- Chapter 8 - Marginality : Representations of Subalternity, Aboriginality and Race -- Chapter 9 - Anthropology and Postcolonialism -- Chapter 10 - Publishing Histories.
Includes bibliographic references and index.
Keywords: African literature (English) -- Publishing -- History -- 20th century; Literature; Publishers and publishing -- Africa -- History -- 20th century; Publishers and publishing -- United Kingdom -- History -- 20th century